Banking Chatbots in Indonesia as AI-Mediated Communication: A CMC and TAM Analysis - Fajrinaldi; Yundira Putri Rahmadianti (Ilomata International Journal of Social Science, 2026)
This study aims to explore how banking AI chatbots mediate communication between banks and customers, and to examine user perceptions regarding the ease of use and usefulness of such technology. Employing a qualitative approach, the research analyzes the experiences of three informants who have interacted with AI chatbot services from Bank Mandiri (MITA), BRI (SABRINA), and BNI (CINTA). The study utilizes the framework of Computer-Mediated Communication (CMC) to assess digital interaction characteristics and adopts the Technology Acceptance Model (TAM) to examine factors of technology acceptance. Findings indicate that banking AI chatbots are perceived as useful and easy to use, especially for routine informational queries. However, they are seen as limited in handling complaints or complex problems. While chatbots provide time flexibility and easy access, the low level of social presence leads to a less empathetic communication experience. Despite these limitations, AI chatbots are accepted as efficient digital communication tools for everyday banking needs. The study highlights the need to enhance chatbot interaction quality to become more human-centered and emotionally responsive.